Cognitive and Academic Functioning of Juvenile Detainees: Implications for Correctional Populations and Public Health. (January 2014) - Lansing, Amy E.; Washburn, Jason J.; Abram, Karen M.; Thomas, Ursula C.; Welty, Leah J.; Teplin, Linda A.
Cognitive functioning affects health. This study assessed cognitive functioning among participants in the Northwestern Juvenile Project, a stratified random sample of 1, 829 newly detained juveniles (10 to 18 years old) from Cook County, Illinois. The study examined receptive vocabulary, oral reading, arithmetic computation skills, and general intellectual abilities. The sample exhibited impaired overall intellectual functioning and deficits in all areas. Males performed more poorly than females. More than three quarters of males showed below average overall intellectual functioning, and 9 in 10 had below average receptive vocabulary skills. Hispanic and African American males performed more poorly than non-Hispanic White males. The multiple systems that serve delinquent youth—correctional, health, legal, and rehabilitative—must collaborate to tailor needed services to the cognitive level of youth in the juvenile justice system.